Structure and directiveness of attitudes to disability - Kaffemaniene, Irena; Jureviciene, Margarita (Social Welfare: Interdisciplinary Approach, 2013)
The study seeks to answer questions: whether the integration of the disabled changes public attitude to people with disabilities? And if so, what is the direction of public opinion change? Representations of disability, understanding of disabled people’s needs and personality traits are analysed using interview and content analysis methods. The study involved students whose future profession is not related to the disabled. The structure of attitude to the disabled is revealed based on the analysis of theoretical (clinical and social) models.